2005
DOI: 10.1074/jbc.m412463200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Guinea Pig 11β-Hydroxysteroid Dehydrogenase Type 1 Provides a Model for Enzyme-Lipid Bilayer Interactions

Abstract: The metabolic reduction of 11-keto groups in glucocorticoid steroids such as cortisone leads to the nuclear receptor ligand cortisol. This conversion is an example of pre-receptor regulation and constitutes a novel pharmacological target for the treatment of metabolic disorders such as insulin resistance and possibly other derangements observed in the metabolic syndrome, such as hyperlipidemia, hypertension, and lowered insulinsecretion.ThisreactioniscarriedoutbytheNADPHdependent type 1 11␤-hydroxysteroid dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 34 publications
3
58
0
Order By: Relevance
“…In this model Cys-175 is found at the N terminus of helix F oriented perpendicular to and in close vicinity to the lipid membrane surface. This region was shown to form a short-chain dehydrogenase dimerization interface (64,67). Because of this structural feature, efficient cross-linking between RPE65 and RDH5 may occur only with the monomeric form of retinol dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…In this model Cys-175 is found at the N terminus of helix F oriented perpendicular to and in close vicinity to the lipid membrane surface. This region was shown to form a short-chain dehydrogenase dimerization interface (64,67). Because of this structural feature, efficient cross-linking between RPE65 and RDH5 may occur only with the monomeric form of retinol dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…11β-HSD1 is a dimeric enzyme, and although a mutant K187N homodimer would be expected to be inactive, the effect of heterodimer formation between WT and mutant subunits (as could occur in heterozygous humans, such as case B) was uncertain. The two subunits of 11β-HSD1 are closely intertwined, facilitating a close structural interplay between the monomers (4,5). Thus, the K187N mutation in one subunit possibly could negatively affect the activity of an adjacent WT subunit.…”
Section: Discussionmentioning
confidence: 99%
“…11β-HSD1 is a member of the short-chain dehydrogenase reductase (SDR) superfamily of enzymes and naturally exists as a homodimer (2)(3)(4)(5), although some studies have suggested that it also may function as a homotetramer (6). Unusually for an SDR enzyme, 11β-HSD1 has an N-terminal membrane anchor (7,8), with a small portion of the N-terminal segment of the enzyme present in the cytosol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although we used a similar cloning and purification procedure, we were unable to displace CHAPS with our adamantane compounds by soaking, cocrystallization or other commonly used complexation procedures. While this is puzzling, another researcher working with guinea pig 11 -HSD1 also reported problems in ligand exchange (Ogg et al, 2005). In this case, the protein was incubated during purification with NADP + and ligand (BVT.4584).…”
Section: Discussionmentioning
confidence: 99%